Analisis Dan Perancangan Sistem Informasi Administrasi Pembayaran Biaya Pendidikan Berbasis Web Dan SMS Gateway Pada Pondok Pesantren Modern Darussalam Mersam - Kurniadi, Rahmad; Devitra, Joni (LPPM Universitas Dinamika Bangsa, 2020)
Darussalam Islamic Boarding School having its address in Sengkati Baru Village, Mersam District,Batanghari Regency, is a pesantren-based religious institution founded in 2003 by KH. M. Ridwan YahyaYasin according to the desire to uphold the symbols of Islam. In the Islamic Boarding School Darussalam,there are obstacles in the process of payment of education costs where the payment process is still using themanual recording system which of course experiences various obstacles. The most common obstacle is thatofficers experience difficulties in recording and reporting to the leadership. Another obstacle that arises isthat the data collection for santri payments requires a long time because payment data is recorded in a bookso that officials must search the data one by one. At present payment information is only conveyed to santri,then santri conveys to parents or guardians. Sometimes some santri do not convey this information to theirparents or guardians, so the parents or guardians of the santri do not know the information about thepayment. From these constraints, the author tries to analyze and design a web-based payment administrationinformation system and sms gateway using the UML (Unified Modeling Language) system modeling method,from a system designed to have user data management features, manage data type of payment, manage data,payment of education costs, manage payment transactions, and manage reports. It is expected to make iteasier for administrators and the Administration in recording the administration of payment of educationcosts and making reports to the leadership.